14.3k views
2 votes
Can someone please help me solve this question? 7-3r=r-4(2+r)

1 Answer

4 votes

Answer:

There is no solution

Explanation:

7−3r=r−4(2+r)

Step 1: Simplify both sides of the equation.

7−3r=r−4(2+r)

7+−3r=r+(−4)(2)+(−4)(r)(Distribute)

7+−3r=r+−8+−4r

−3r+7=(r+−4r)+(−8)(Combine Like Terms)

−3r+7=−3r+−8

−3r+7=−3r−8

Step 2: Add 3r to both sides.

−3r+7+3r=−3r−8+3r

7=−8

Step 3: Subtract 7 from both sides.

7−7=−8−7

0=−15

Answer:

There are no solutions.

User Attrachii
by
4.7k points